Synthesis of SrCO3 Nanoparticles Supported on Montmorillonite as Efficient Catalyst in the Preparation of α, α-bis(substituted benzylidene) cycloalkanones - Mohammadpour, Azim; Sheikhhosseini, Enayatollah (Letters in Organic Chemistry, 2022)
In the present study, the SrCO3@montmorillonite nanocomposite was synthesized by loading Sr(NO3)2 on natural bentonite using a controlled and facile microwave method. The SrCO3@montmorillonite nanoparticles’ characteristics are identified using advanced techniques, such as infrared spectroscopy (IR), energy-dispersive X-ray analysis (EDX), X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), and pore size distribution analysis. Crossed-aldol condensation of an aromatic aldehyde with cycloalkanone in the presence of these nanoparticles produced α, α-bis(substituted-benzylidene) cycloalkanones in good yields without using any solvent. The present method is operationally simple and dose not use organic solvent, which makes the process environmentally benign.
Keywords: bentonite